Amperometric Sarcosine Biosensor Based on a Bi-Functional Platinum-Loaded Organic-Inorganic Hybrid Tungsten Phosphonate Material. Issue 5 (1st May 2022) - Shi, Xinlin; Chen, Xiaohui; Zuo, Wanying; Lin, Luyin; Xiao, Wenhuang; Yang, Haipeng
Abstract : Sarcosine has been identified as an effective biomarker for prostate cancer. However, the rapid and accurate determination of sarcosine has been a challenge due to its low concentration and the presence of interfering substances in human serum. Here we depict an amperometric sarcosine biosensor by using organic-inorganic hybrid mesoporous tungsten phosphonate (MTP) material. The MTP was synthesized by using a soft-template method, and platinum (Pt) nanoparticles were loaded onto it by using the ethylene glycol reduction method. Due to the excellent anti-interference performance of the mesoporous tungsten phosphonate and the high electrocatalytic activity of Pt nanoparticles, the as-prepared material exhibited both anti-interference function and electrocatalytic function. A simple biosensor was obtained by modifying a glassy carbon electrode (GCE) with the bi-functional material and sarcosine oxidase (SOx). The biosensor had a linear detection range of 1–71 μ M with a limit of detection (LOD) of 0.4 μ M, and had good ability to exclude interference signals from common interfering substances. Compared with our previous work about nickel phosphonate and molybdenum phosphonate, though the mechanism that the metal ions affects the anti-interference performance of the biosensor is not clear yet, it is reasonable to expect better anti-interference performance by replacing the metal ions in the phosphonate materials.